2017
DOI: 10.1001/jama.2017.2068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Total Laparoscopic Hysterectomy vs Total Abdominal Hysterectomy on Disease-Free Survival Among Women With Stage I Endometrial Cancer

Abstract: clinicaltrials.gov Identifier: NCT00096408; Australian New Zealand Clinical Trials Registry: CTRN12606000261516.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
219
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 320 publications
(257 citation statements)
references
References 31 publications
9
219
0
5
Order By: Relevance
“…Data on 3-year DFS and HRs could be extracted from 5 studies. 3,4,17,19,23 Most studies did not report details of the randomization method, but it was assumed that allocation concealment was not compromised. All analyses were on an intention to treat basis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data on 3-year DFS and HRs could be extracted from 5 studies. 3,4,17,19,23 Most studies did not report details of the randomization method, but it was assumed that allocation concealment was not compromised. All analyses were on an intention to treat basis.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the trials by year of commencement, and Table 2, a summary of outcomes. Four studies reported results for all survival outcomes of interest 3,17,20,23 : LR, DFS, and OS. One study reported results for DFS and LR, 4 and 1 study reported OS and LR 15 ; we were unable to obtain DFS outcomes from the authors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations